La administración pública como organizadora y gestora de la igualdad - Garrido Gómez, María Isabel (2015)
This paper reveals that the action of the Public Administration has changed over recent years and that, largely, it has now become a managing body partly regulated by a pseudo-private Law. Consequently, this evidences a governance form arising as a network together with private organizations and the civil society. In this regard, Administrative Law regulations function in interaction with business rules, trade unions demands on the defense of workers’ functions and interests, together with the informal rules of the political parties. In any case, this can be seen in the fact that many of the rules that today regulate the Administration are aimed at expanding the capitalist economic organization and the disappearance of frontiers, about financial flows or the market of goods and services. This is why it is so important to consider the established guidelines and to ensure that the search for equality is both real and effective.